Community-Based Approaches to Fisheries Management in MSMEs: A Bibliometric Exploration - Zayafika Mareta; Muhammad Arif; Pardin Lasaksi; Nursyam Ar (West Science Social and Humanities Studies, 2024)
This study conducts a bibliometric exploration of community-based approaches to fisheries management within the context of Micro, Small, and Medium Enterprises (MSMEs). By analyzing scholarly publications from multiple databases, the research highlights key themes, challenges, and emerging trends in sustainable fisheries management. The study identifies significant clusters of research themes through network visualizations and discusses the socio-economic impacts of community-based strategies on local fisheries management. It underscores the necessity of integrating local knowledge and practices in MSMEs to enhance sustainability and resilience against global challenges like climate change and market fluctuations. Through this exploration, the paper aims to contribute to policy development and practical interventions that promote sustainable fisheries practices and bolster MSME resilience.